2021
DOI: 10.21106/ijtmrph.319
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Female Genital Mutilation or Cutting Among Daughters of Women in Guinea, West Africa

Abstract: Background and Objective: In some African countries like Guinea, female genital mutilation/cutting (FGM/C) has been considered as an essential social norm in ensuring girls’ and women’s virginity by reducing their sexual desires. This study aimed at examining the factors associated with FGM/C among daughters of women aged 15-49 in Guinea. Methods: Using the 2018 Guinea Demographic and Health Survey, we analyzed data on 10,721 women of reproductive age (15-49 years) who had at least one daughter. A two-level mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
2
3
1
Order By: Relevance
“…We controlled for the influence of other factors-mother's age, religion, marital status, whether FGM/C is an important religious practice, place of residence and household wealth. Our findings of reducing odds of daughter's circumcision with increasing mother's age contradicts what has been reported in existing literature [37,41]. In the study's sample, almost half of women aged less than 25 years (45%) had circumcised their daughters and this was high relative to the other age categories.…”
Section: Discussioncontrasting
confidence: 99%
“…We controlled for the influence of other factors-mother's age, religion, marital status, whether FGM/C is an important religious practice, place of residence and household wealth. Our findings of reducing odds of daughter's circumcision with increasing mother's age contradicts what has been reported in existing literature [37,41]. In the study's sample, almost half of women aged less than 25 years (45%) had circumcised their daughters and this was high relative to the other age categories.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, as compared to the household with the richest wealth quintile, the probabilities of circumcision were increased by 3.65 in the household with the poorest wealth quintile. This finding is in line with studies done in Ethiopia, 18 Sierra Leone 20,30 and Guinea. 20,30 Mothers in the poorest wealth quintile might experience this because they are more likely than mothers in the greatest wealth quintile to get knowledge regarding the effects of female genital mutilation in an interrupted manner.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with studies done in Ethiopia, 18 Sierra Leone 20,30 and Guinea. 20,30 Mothers in the poorest wealth quintile might experience this because they are more likely than mothers in the greatest wealth quintile to get knowledge regarding the effects of female genital mutilation in an interrupted manner. In comparison to mothers in the highest wealth quintile, those mothers also lack the ability to make decisions on the cessation of the practice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in line with the findings of previous studies that identified improved socio-economic status as protective against the circumcision of girls, while demographic factors such as increasing age, being married and a woman's experience of FGM increase the likelihood of circumcision of daughters. 26 , 28 , 57 These findings imply that eliminating FGM in SSA goes beyond encouraging ANC attendance and health facility delivery to improving the socio-economic status of women and educating married, circumcised and older women about the negative effects of this cultural practice.…”
Section: Discussionmentioning
confidence: 99%